2007
DOI: 10.1002/ijc.22726
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in women in Shenzhen City, People's Republic of China, a population typical of recent Chinese urbanisation

Abstract: Select cancer registries report that cervical cancer is relatively rare in the People's Republic of China, but may not be representative of the entire country. We carried out a survey of human papillomavirus (HPV) prevalence in 3 samples of women, i.e., general population, factory workers, and tertiary sector workers, in Shenzhen City in 2004. All participants were interviewed and offered gynaecological examination. HPV detection in exfoliated cervical cells was performed using a GP5þ/6þ PCR-based assay. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
61
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 25 publications
(37 reference statements)
29
61
7
Order By: Relevance
“…HPV52 and 58, however, were not as predominant as in similar surveys in China [16][17][18]. We also confirmed that the type distribution Major strengths of our present study include a large and population-based sample, the use of a standardized and well-validated HPV test allowing comparisons with similar studies around the world [9] and the presence of a concurrent series of women with ICC drawn from the same study area.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…HPV52 and 58, however, were not as predominant as in similar surveys in China [16][17][18]. We also confirmed that the type distribution Major strengths of our present study include a large and population-based sample, the use of a standardized and well-validated HPV test allowing comparisons with similar studies around the world [9] and the presence of a concurrent series of women with ICC drawn from the same study area.…”
Section: Discussionsupporting
confidence: 83%
“…The agespecific curve of HPV prevalence in Nepal resembled the flat age curves reported previously in some low-resource countries in Asia and Africa [15][16][17][18]24], albeit at a lower level of HPV prevalence. It clearly differed, on the other hand, from the steep decrease in HPV prevalence seen by age in high-and medium-resource countries in Europe, the Americas, and Asia [23,25].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations